Solomon Islands : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Solomon Islands. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that the economy of the Solomon Islands grew by 3.5 percent in 2016 driven by a peak in the forestry sector. Growth remained solid in 2017 and is projected at 3.0 for 2018, buoyed by infrastructure spending, fisheries and agriculture, although logging production is slowing down. Inflation is contained at an annual rate of just 1.6 percent in October 2017. The current account deficit has widened a little but international reserves levels are comfortable. The fiscal deficit is expected to have reached 4.0 percent of GDP in 2017 and to widen further in 2018. The risks to the economy are on the downside with the weakening fiscal position heightening vulnerability to shocks.